A vanadium-based oxide-phosphate-pyrophosphate framework as a 4 V electrode material for K-ion batteries. Issue 37 (23rd August 2021) - Ohara, Mirai; Hameed, A. Shahul; Kubota, Kei; Katogi, Akihiro; Chihara, Kuniko; Hosaka, Tomooki; Komaba, Shinichi
Abstract : Highly pure K6 (VO)2 (V2 O3 )2 (PO4 )4 (P2 O7 ), synthesized from the oxalatophosphate precursor, demonstrates a reversible potassium extraction/insertion capacity of 59 mA h g −1 with a single discharge voltage plateau at 4.0 V at room temperature. Abstract : K-ion batteries (KIBs) are promising for large-scale electrical energy storage owing to the abundant resources and the electrochemical specificity of potassium. Among the positive electrode materials for KIBs, vanadium-based polyanionic materials are interesting because of their high working voltage and good structural stability which dictates the cycle life. In this study, a potassium vanadium oxide phosphate, K6 (VO)2 (V2 O3 )2 (PO4 )4 (P2 O7 ), has been investigated as a 4 V class positive electrode material for non-aqueous KIBs. The material is synthesized through pyrolysis of a single metal–organic molecular precursor, K2 [(VOHPO4 )2 (C2 O4 )] at 500 °C in air. The material demonstrates a reversible extraction/insertion of 2.7 mol of potassium from/into the structure at a discharge voltage of ∼4.03 V vs. K. Operando and ex situ powder X-ray diffraction analyses reveal that the material undergoes reversible K extraction/insertion during charge/discharge via a two-phase reaction mechanism. Despite the extraction/insertion of large potassium ions, the material demonstrates an insignificant volume change of ∼1.2% during charge/discharge resulting in excellent cycling stability without capacity degradation over 100 cycles in a highly concentrated electrolyte cell. Robustness of the polyanionic framework is proved from identical XRD patterns of the pristine and cycled electrodes (after 100 cycles).